Desain Model Manajemen Layanan TI berbasis Information Technology Infrastructure Library (ITIL) - Gunawan, Hendro (MEANS (Media Informasi Analisa dan Sistem), 2019)
Along with the increasing need for services in organizations, especially in the field of Information Technology (IT), the IT paradigm which initially only focused on data processing and manipulation, is now beginning to shift to strategic planning and IT services. IT Service Management (ITSM) is a method of managing information technology systems that seek to align IT with business needs to manage the provision of efficient IT services with quality assurance. ITIL (Information Technology Infrastructure Library) is one of the Frameworks in ITSM, ITIL is a popular / widely used Framework in ITSM research. Atma Jaya Yogyakarta University (UAJY) is one of the major private universities in Yogyakarta and is also increasingly complex in providing services to its academic community. The use of IT in UAJY is manifested in a variety of services that can support the needs of every user. This research resulted in an IT service design that will be used by students and lecturers. This research focuses on the Service Design phase which will produce a Service Design Package (SDP) using the ITIL Framework.